2014
DOI: 10.2478/amm-2014-0288
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Neural Networks for Studying Phase Transformation by the Method of Acoustic Emission in Bearing Steel/ Zastosowanie Sieci Neuronowych Do Badania Przemian Fazowych W Stali Łożyskowej Metodą Emisji Akustycznej

Abstract: The research was carried out on steel l00CrMnSi6-4 under isothermal austempering resulting in forming the duplex structure: martensitic and bainitic. The kinetics of transformation was controlled by the acoustic emission method. Complex phase transformations caused by segregation and carbide banding occur at the low-temperature heat treatment of bearing steel. At the temperature close to M S , a certain temperature range occurs where an effect of the first product of prior athermal martensite on the bainitic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In [32,33,34] ANNs were used to analyse the results of testing concrete by means of non-destructive methods. Łazarska et al [35] and Woźniak et al [36] in their investigations of steel successfully used the acoustic emission method and artificial neural networks to analyse the obtained results. Rucka and Wilde [37,38], Zielińska and Rucka [39] and Wojtczak and Rucka [40] successfully used the ultrasonic method to investigate damage to concrete structures and masonry pillars.…”
Section: Literature Surveymentioning
confidence: 99%
“…In [32,33,34] ANNs were used to analyse the results of testing concrete by means of non-destructive methods. Łazarska et al [35] and Woźniak et al [36] in their investigations of steel successfully used the acoustic emission method and artificial neural networks to analyse the obtained results. Rucka and Wilde [37,38], Zielińska and Rucka [39] and Wojtczak and Rucka [40] successfully used the ultrasonic method to investigate damage to concrete structures and masonry pillars.…”
Section: Literature Surveymentioning
confidence: 99%
“…In paper [29], Schabowicz used ANNs to analyse the results of nondestructive tests carried out on concrete. Łazarska et al [30] and Woźniak et al [31] successfully used the acoustic emission method and artificial neural networks to analyse its results. Rucka and Wilde [32,33] successfully used the ultrasonic method to investigate damage to concrete structures.…”
Section: Survey Of the Literaturementioning
confidence: 99%
“…2. Illustration of heat treatment during the experiment carried out on the stand for AE testing and the marked time periods [16] AE signals received using the sensor were sent to the analyser where the signal was received and sent to a central unit. A scheme of the stand for AE tests is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bhadeshia [12,13] showed that the kinetics of bainitic transformation is controlled by a nucleation rate. Research related to the kinetics of bainitic transformation were also carried out by T.Z.Woźniak [14][15][16], who proposed a model of transformation mechanism to separate C-curves.…”
Section: Introductionmentioning
confidence: 99%